2016
DOI: 10.2106/jbjs.15.00425
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Percutaneous Vertebroplasty and Conservative Therapy for Treating Osteoporotic Compression Fractures in the Thoracic and Lumbar Spine

Abstract: Up to 1 year postoperatively, the effect of PVP exceeded the effect of conservative therapy with respect to pain relief in patients with osteoporotic compression fractures. The effect size was significant and close to the minimal clinically important difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…There were also insufficient data to determine differences in extravasation rates or serious adverse events. We demonstrated comparable findings to those of a recent meta-analysis comparing NSM with VP by Mattie et al 60 When evaluating 11 studies containing 1048 participants, Mattie et al 60 reported VP was better than NSM with respect to pain relief up to 1 year after VP. This provides additional information supportive of the efficacy of VP, similar to previous meta-analyses by Anderson et al 53 and Papanastassiou et al 52 and trends shown in several of the 25 articles included in this meta-analysis.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…There were also insufficient data to determine differences in extravasation rates or serious adverse events. We demonstrated comparable findings to those of a recent meta-analysis comparing NSM with VP by Mattie et al 60 When evaluating 11 studies containing 1048 participants, Mattie et al 60 reported VP was better than NSM with respect to pain relief up to 1 year after VP. This provides additional information supportive of the efficacy of VP, similar to previous meta-analyses by Anderson et al 53 and Papanastassiou et al 52 and trends shown in several of the 25 articles included in this meta-analysis.…”
Section: Resultssupporting
confidence: 86%
“…This provides additional information supportive of the efficacy of VP, similar to previous meta-analyses by Anderson et al 53 and Papanastassiou et al 52 and trends shown in several of the 25 articles included in this meta-analysis. The level of evidence of the meta-analysis of Mattie et al 60 was designated as Oxford Level I, which should be taken into account by not only treatment guidelines but also policy recommendations and HTAs. The meta-analysis also focused specifically on percutaneous vertebroplasty as compared with conservative therapy, while only evaluating studies in which the primary outcome was pain relief.…”
Section: Resultsmentioning
confidence: 99%
“…Percutaneous vertebroplasty (PV) is a well-established treatment for stabilization of vertebral bodies in both vertebral fractures and vertebral metastasis (1). Osteoporosis is the most common cause of fractures occurring at different anatomical sites, and one of the most common is fracture of vertebral bodies (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 10 meta-analyses, three compared both VP and KP against control cohort [8][9][10] and seven compared VP to control cohorts. [11][12][13][14][15][16][17] Characteristics and findings of the 10 studies are summarized in Table 1. When combined, the 10 meta-analyses examined a total of 22 trials.…”
Section: Description Of Studiesmentioning
confidence: 99%